David gets in trouble - Shannon, David, 1959- (New York : Blue Sky Press, 2002)
When David gets in trouble, he has excuses right up until bedtime, when he realizes he really is sorry.
Pub Weekly
1.3
K-3
Keywords: Behavior -- Fiction; Apologizing -- Fiction; Human behavior -- Fiction; Apologizing -- Fiction